An Application of Fintech for A Modern Islamic Financial Industry: Challenges and Practical Solutions - Wan Hasanah Megat Ajib (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2022)
Fintech can be defined as a digital financial service by using sophisticated technologies through software systems. This paper aims to define Fintech in an understandable definition. This study also attempts to find out the challenges of Fintech application in the modern Islamic financial industry. Then, practical solutions are recommended in this paper to address the arising current challenges to ensure the maximization of Fintech usage in a modern Islamic financial industry. This paper relies on past literature, past studies, published reports, online news, and official website portals related to the topic. The qualitative method is used for this study by reviewing the collected past literature reviews to achieve the objective of the research. Hence, the findings revealed that there are 12 challenges of Fintech application encountered by the Islamic financial industry; ; (1) Regulation framework; (2) Human resources; (3) Sharia-compliant issue; (4) Security risk; (5) High competition from Fintech Firms; (6) Clients’ and Investors’ trust; (7) Adaptation of new Fintech tools; (8) Government support; (9) Lack of IT skills by the client; (10) Lack of technology and capital venture; (11) Islamic Financial Business Model and its management; and lastly (12) Penetration of international market. Next, practical solutions are suggested for every Fintech challenge to achieve the second research objective of this paper. The practical solutions are targeted to the national and global policymakers. This paper helps to improve Fintech usage in the Islamic financial industry with the latest sophisticated technologies to be able to sustain in the market while maintaining its reputation.